Heat and performance of flow field near three-dimensional jets in the presence of exposure - Isatayev, M. S.; Isatayev, S. I.; Toleuov, G.; Zulbuharova, E. M. (Recent Contributions to Physics, 2013)
The aim of this work is the experimental investigation of the coherent structure of turbulence in a three-dimensional jet, their maximum range. It was found that the jet streams originally appeared vortices can decay into smaller and mutually interacting with each other and merge to form a large conglomerate of eddies that retain their individuality until about the decay of the jet in the direction of flow. Experimentally, we have shown that the maximum frequency of turbulent fluctuations do not exceed the frequency of the primary large-scale vortices formed in the initial section of the jet stream.When studying the three-dimensional jets previously defined effect of initial conditions and parameters the expiry of the control action on the velocity and temperature distribution along the jet and the cross sections of flow. For an explanation of the features found in the form of distributions to a more detailed study of the structure of organizedmovements in three-dimensional flow field near the jets. This work is a continuation of studies aimed at identifying the role of organized vortex motions in the processes of mixing and heat transfer in the jet stream.
Keywords: flat free jet; large-scale vortices; turbulence; velocity and temperature; range